Water productivity of summer mungbean (Vigna radiata) in relation to irrigation, tillage and mulch in sandy loam and loamy sand soils - MADAD, SHANTNU; DHALIWAL, JEEVANJOT; DHINGRA, MADHU; SINGH, C B; KAHLON, M S (The Indian Journal of Agricultural Sciences, 2023)
There is a growing interest among the farmers of the state to take an additional crop, i.e. summer mungbean (Vigna radiata L.) in the window period of rice (Oryza sativa L.)-wheat (Triticum aestivum L.) system with a little emphasis on the water productivity of summer mungbean. The present study was aimed to assess the water productivity of summer mungbean under differential irrigation regimes, tillage and mulch in sandy loam and loamy sand soils. A field experiment was conducted during the summer 2021 and 2022 with three irrigation regimes (based on irrigation water to PAN-E ratio of 0.75 (I0.75), 0.50 (I0.50), 0.25 (I0.25) in sandy loam and 0.8 (I0.8), 0.6 (I0.6) and 0.4 (I0.4) in loamy sand soils, two tillage systems, viz. deep tillage and conventional tillage; and two mulch rates (no mulch and application of rice straw mulch @6 t/ha). Irrigation regime, I0.75 and I0.8 resulted in higher crop biomass, however the seed yield and water productivity were highest under I0.50 and I0.6. Deep tillage with mulch resulted in higher seed yield and water productivity in comparison to conventional tillage with no mulch. Medium irrigated regime (I0.50 and I0.6) coupled with deep tillage and rice straw mulch was found to be effective in improving the seed yield of mung bean in loamy sand soils in north-west India.